MULTIVARIATE MORPHOMETRICS AND ALLOMETRY IN A POLYMORPHIC ANT - Diniz, JAF; Vonzuben, C. J.; Fowler, H. G.; Schlindwein, M. N.; Bueno, O. C. (Birkhauser Verlag Ag, 1994)
In this paper we describe how morphological castes can be distinguished using multivariate statistical methods combined with jackknife estimators of the allometric coefficients. Data from the polymorphic ant, Camponotus rufipes, produced two distinct patterns of allometric variation, and thus two morphological castes. Morphometric analysis distinguished different allometric patterns within the two castes, with overall variability being greater in the major workers. Caste-specific scaling variabilities were associated with the relative importance of first principal component. The static multivariate allometric coefficients for each of 10 measured characters were different between castes, but their relative magnitudes within castes were similar. Multivariate statistical analysis of worker polymorphism in ants is a more complete descriptor of shape variation than, and provides statistical and conceptual advantages over, the standard bivariate techniques commonly used.
Keywords: CASTE; ANT; MORPHOMETRICS; PRINCIPAL COMPONENT ANALYSIS; JACKKNIFE ESTIMATES